Respuesta :

A=34
B= -681
C= -28
D= -2
E = -39
F= 181

Hope this helps!
Tsuha

Step-by-step explanation:

—Math

a) –2 + (–3) x (–8 + 4)

= –2 + (–3) x (–4)

= –2 + 12

= 10

b) –9 –(–8) x 7 + [6 x (-2)]

= –9 + 8 x 7 + (-12)

= –9 + 56 –12

= 35

c) 7 x [8 –(–2) x (–6)]

= 7 x (8 + 2 x (–6)

= 7 x (8 –12)

= 7 x (–4)

= –28

d) –6 : (–3) – [8 : (–2)]

= 2 – (–4)

= 2 + 4

= 6

e) 0+ (–4) – 7 x 5

= –4 –35

= –39

f) [–14 + (–23)] – [(–17 –2) x 10]

= –37 – (–19 x 10)

= –37 –(– 190)

= –37 + 190

= –153

pick me as the brainliest